Active entrepreneurship education and the impact on approaches to learning: Mixed methods evidence from a six-year study into one entrepreneurship educator's classroom. Issue 4 (August 2021) - Curtis, Vic; Moon, Rob; Penaluna, Andy
Taking an active and experiential approach to teaching is often assumed to be the best way to promote learning. However, the empirical evidence to support this assertion in entrepreneurship education is inconclusive, and current practice suggests that delivery in higher education is still quite passive and traditional. This 6-year, mixed method study sets out to demonstrate that, in a final-year International Entrepreneurship module at a UK university mapped through the lens of 'about', 'for' and 'through' entrepreneurship, a more innovative, active, experiential and constructively aligned approach to teaching, learning and assessment impacts positively on students' deep and surface approaches to learning. Students viewed the module as significantly more active than passive and the level of deep learning was significantly greater than the level of surface learning. Additionally, the more active approach was significantly correlated to increased deep learning and reduced surface learning. Students highlighted the active teaching approach and the creation of videos for a local company as part of the authentic assessment as catalysts for deeper learning approaches. The study provides empirical evidence that active entrepreneurship education has a positive impact on student approaches to learning.